Kinerja Pendapatan dan Belanja Kota Malang Tahun 2018–2023 - Mega Tunjung Hapsari; Dhea Ni’matul Maula; Dini Ayuningtyas; Dwi Haziza Tussholeha; Egista Yessandrina Setiyorini; Nadia Alifatul Isna (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Evaluation of Regional Government financial performance is important and needs to be carried out. The aim of this research is to check the financial performance of the Malang City Government by analyzing financial reports from 2018 to 2023. This research is descriptive qualitative with secondary data obtained from the Malang City Central Statistics Agency. The results show that the degree of decentralization ratio has an average of Fair Performance, the financial independence ratio has an average of Low Performance, the efficiency ratio has an average of Inefficient Performance, the ratio of operational expenditure to total expenditure has an average of Good Performance, the ratio of capital expenditure to total expenditure with average Good Performance, and ratio of expenditure growth with average Good Performance.